Classifier Constructions in English and Kurdish - Sabir, Anjuman M.; Kamal, Dyar A. (Humanities Journal of University of Zakho, 2019)
Greenberg (1972) in a study based on a sample of about 100 languages with numeral classifiers, attempted to determine the conditions under which anon- classifier language might become a classifier language. Later Hale and Shresthachrya (1973) made their attempts to seek whether Newari is considered as a classifier language or not. The purpose of this study is to analyze the Kurdish classifier system based on the Greenberg (1972) whether Kurdish is a classifier language or not, the paper also compares classifier constructions in English and Kurdish, with the aim of addressing the research questions: what linguistic devices are used in Kurdish and English for classification? How different or similar are classifiers in Kurdish and English as non-classifier language. Classifiers in Kurdish have not been studied extensively and there are not any references available on classifiers of Kurdish in English. Therefore, by considering the classifier system of Kurdish, this study makes attempt to provide an introductory source of analytical research of grammar in Kurdish.